8. The Role of Bovine Viral Diarrhea Virus In Bovine Respiratory Disease Complex In Cattle Import Livestock At 2019 Periode - J Susilo; J Siswanto; T. Fadrial Karmil; Rusli Rusli; M. Nur Salim; Zainuddin Zainuddin; Ginta Riady; Dasrul Dasrul; Fakhrurrazi Fakhrurrazi; Azhari Azhari; Andi Novita (Jurnal Medika Veterinaria, 2020)
Bovine viral diarrhea virus (BVDV) is one of the most important infectious diseases in cattle breeding. Bovine respiratory disease complex (BRDC) is a respiratory disease in mature and calf cattle which is a viral and bacterial superinfection including BVDV. The purpose of reseach is to study the role of BVDV in cases of Bovine respiratory disease complex (BRDC), especially with the characteristic of lesions were granulomatous pneumonia. The material in this study was lung tissue that was fixed with 10% formaldehyde buffer of calf sampel collected in October and November 2019. The sample is processed in a pathology laboratory for hematoxyline eosin (HE) staining and followed by immunohistochemical staining (IHC). A total of 11 lung samples sent from imported beef cattle and dairy cattle with a diagnosis of pneumonia complex morphology continued with CPI testing with monoclonal antibodies against bovine viral diarrhea virus. Nine samples showed positive CPI results against BVDV and two other samples were negative. Bovine viral diarrhea virus is detected in all granulomatous pneumonia, so it has an important role in BRDC. Early detection, treatment and prevention of BRDC affected or followed by BVDV must be carried out programmatically.